Advanced liver fibrosis, but not MASLD, is associated with accelerated biological aging: a population-based study - Chengcheng Tong; Yufeng Xue; Wei Wang; Xi Chen (BMC, 2024)
Abstract Background The process of biological aging in patients diagnosed with chronic liver disease remains unclear. Aim The current study aims to investigate if there is an accelerated biological aging process in participants with advanced fibrosis (AF) and metabolic dysfunction-associated steatotic liver disease (MASLD). Methods Data from the 2017-2018 NHANES cycle were analyzed. AF was determined based on the values of liver stiffness measurement (LSM) and MASLD was defined according to new consensus nomenclature. Klemera-Doubal method biological age (KDM bioage) and Phenotypic age (Phenoage) were adopted to quantify biological age. Phenoage advancement (Phenoage_advance) and KDM advancement (KDM_advance) were generated as the difference between the calculated biological age and chronological age, and a positive residual was regarded as an indicator of accelerated biological aging. Results A total of 3974 participants was enrolled. The weight mean KDM_advance and phenoage_advance in AF group was 4.22 years (95%CI: 2.96-5.49 years) and 2.61 years (95%CI: 1.80-3.41 years), while in MASLD group was 0.37 years (95%CI: -0.28-1.03 years) and 0.04 years (95%CI: -0.64-0.72 years), respectively. Multivariate linear regression analysis showed that participants with AF had older KDM_advance and phenoage_advance compared with those without AF (1.50 years (95%CI: 0.23-2.77 years), P = 0.02; 1.00 years (95%CI: 0.18-1.82 years), P = 0.02; respectively), in models adjusting demographic characteristics, socioeconomic status, lifestyle factors, and comorbidities. No significant association was found between MASLD and KDM_advance and phenoage_advance. Conclusions AF, not MASLD, was independently associated with accelerated biological aging in adults from a US representative sample.